Analisis Respon Sosial Terhadap Kristenisasi Berkedok Pernikahan: (Studi Kasus Masyarakat Kabupaten Bengkayang Kalimantan Barat) - Muzdalifah, Siti; Ashari, Winning Son (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2024)
Christianization is a religious movement that emerged after the end of the crusades. The goal is to spread Christianity to all people in the world, especially to Muslims. One way of spreading Christianization is through marriage, as allegedly happened in Bengkayang Regency. The purpose of this study is to analyze the community's response to the alleged Christianization under the guise of marriage that occurred in Bengkayang Regency, West Kalimantan, the role of the community in preventing this, and community suggestions to minimize this. This research uses a qualitative approach with a case study type. Data was obtained directly from the community as the first source. The results of this study indicate that (1) there are differences of opinion among the community regarding the many phenomena of Muslims who become apostates through marriage in Bengkayang district, (2) 4 ways of preventing the community from anticipating Christianization through marriage were found, (3) 7 suggestions from the community were found to minimize the occurrence of apostasy through marriage.